Why some firms export? An empirical analysis for manufacturing firms in the MENA region - Ali Fakih; Pascal L. Ghazalian (Institute for the Study of Labor (IZA), 2013)
This paper analyzes the exporting behaviour of manufacturing firms located in the Middle East and North Africa (MENA) region using data from the World Bank's Enterprise Surveys Database. It specifically examines the factors that determine the probability of exporting and the export intensity of these firms. The empirical specification is represented through a country-specific effect model and through a model with country variables. The empirical results reveal significant positive effects of private foreign ownership, information and communication technology, and firm size on the probability of exporting and on export intensity of MENA manufacturing firms. Government ownership and the relative labour compositions of firms in terms of skilled production workers and in terms of non-production workers tend to exert negative effects on firms' propensity to export. The empirical results from the model with country variables underscore the enhancing effects of national economic development factors on the probability of exporting and on export intensity. Also, they indicate that the propensity to export of these firms decreases with larger domestic market size. The empirical analysis reveals considerable variations in the effects of the determining factors when carrying out the estimation for individual countries.
Keywords: F1; F4; F14; 330; exporting decision; export intensity; probit model; fractional logit model; MENA region